Museums and Archeology: some reflections (Cadernos de Sociomuseologia, 2017)
This article results from a preliminary thoughts about museums of archeology that part of the observation of the museum sector in Brazil, but it might eventually extend to contexts in which the preservation of archaeological heritage and musealization references are affected by the dynamics of Contract Archaeology. The aim of this paper is to initiate a reflection on some conceptual and methodological issues relating to archaeological museums, notably the specifics of this kind of museum, the theme can be approached, the profile of museums that adopt the grammar of Sociomuseologia and Public Archaeology applying museographic strategies to decrease the gap between the discourse of the permanent exhibitions in the development of archaeological research and the challenges of managing archeological collections from the development of Contract Archaeology. The methodology focuses on the literature review on the subject and empirical observation about the Brazilian context. Considerations to highlightthis preliminary thoughts concerning the urgency of establishing an agenda for collective and collaborative work of the various professionals involved in the processes of preservation of archaeological heritage museums to exert their full power while loci of appropriation and reinterpretation of the archaeological heritage references.Keywords: museums, Archaeology, Sociomuseologia, Public Archaeology